2003
DOI: 10.1177/147323000303100211
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiological Features of Ulcerative Colitis in Trakya, Turkey

Abstract: To determine the epidemiological features of ulcerative colitis in the Trakya region of Turkey, southeast Europe, we conducted a descriptive, cross-sectional, hospital-based study. All subjects were followed, and age, sex, place of residence, family history, educational status, tobacco consumption and use of oral contraceptives were recorded. The study included 49 cases of ulcerative colitis. The incidence of the disease was 0.59 per 100,000 in 1998, 0.89 per 100,000 in 1999, 0.89 per 100,000 in 2000 and 0.69 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
1
20

Year Published

2005
2005
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(42 citation statements)
references
References 23 publications
0
21
1
20
Order By: Relevance
“…IBD was evident in 11.2% of cases, ulcerative colitis represented most of them (10.4%) while Crohn's disease was evident in just two cases in the sample with percent of 0.8%.This means that the UC/CD ratio is 13:1. Table ( 4) shows that with comparison between the IBD patients and other patients showed that they were significantly younger and the percentage of females among them was significantly higher and the percentage of smokers and comorbidities also was significantly lower. Table 6 shows that most cases of ulcerative colitis had only proctitis about 50%, with mild severity 42%.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…IBD was evident in 11.2% of cases, ulcerative colitis represented most of them (10.4%) while Crohn's disease was evident in just two cases in the sample with percent of 0.8%.This means that the UC/CD ratio is 13:1. Table ( 4) shows that with comparison between the IBD patients and other patients showed that they were significantly younger and the percentage of females among them was significantly higher and the percentage of smokers and comorbidities also was significantly lower. Table 6 shows that most cases of ulcerative colitis had only proctitis about 50%, with mild severity 42%.…”
Section: Discussionmentioning
confidence: 98%
“…IBD have also emerged in countries in which it had rarely been previously reported, including South Korea, China, India and North Africa [3]. The incidence in the Mediterranean countries is about 5/100,000 persons [4]. The epidemiological characters of IBD in Egypt is similar to those in Asian and African population with UC/CD ratio of 6:1.…”
Section: Introductionmentioning
confidence: 89%
“…Similarly, a retrospective study from the same region estimated a 0.94/10 5 mean incidence of CD in 1983-2002, with a gradual increase in incidence from 0.32/10 5 to 1.66/10 5 [29] . In contrast, in Turkey the incidence of UC was as low as 0.59/10 5 -0.69/10 5 between 1998 and 2001, in a hospital-based study [30] . Finally, a recent case series from Teheran, Iran suggests very low incidence rates, since authors reported that only 448 IBD patients were referred to or diagnosed in two university hospitals and two private GI clinics between 1992 and 2002 [31] .…”
Section: Incidence Of Ibd In Other Parts Of the World: East Europe Amentioning
confidence: 90%
“…Most of the earlier studies from Eastern Europe, and still the majority of studies from Asia [19,23] , Middle-East [29,30] and Central America [33] are biased by methodological shortcomings. A great majority of them were retrospective, hospital-based surveys, which may have at least partly been responsible for the low incidence rates reported.…”
Section: How Can We Explain the Recent Epidemiological Trends?mentioning
confidence: 99%
“…Bu nedenle ülkemiz İBH açısından bir köprü vazifesi görmektedir. Son 10 yıl içerisinde Türkiye'de İBH'nın epidemiyolojisi ile ilgili yapılmış birkaç çalışma bulunmaktadır (21)(22)(23)(24) Türkiye'deki diğer çalışmalarla benzerlik gös-terirken, prevalansta belirgin yükseklik izlenmektedir.…”
unclassified